Meditation in the school environment “uncertainties and reflections” (Revista Electrónica REDINE, 2024)
Meditation is a millennial Eastern technique, with debatable and imprecise origins, that has for several decades provided benefits linked to tranquility, inner peace and overall human health. Reason why, it has been of permanent interest, in our globalized world. Its dissemination, in martial, sporting, social and even religious venues, demonstrates the importance of literacy and practicality. However, in the school setting its incorporation and acceptance has been minuscule, possibly due to some principles and habits of our Western culture. It is due to the inexperience of the educational authorities and the teachers responsible for carrying out the teaching and learning process. In the face of this reality, the present essay, highlights certain uncertainties and reflections, generated from a grounded bibliographical review on meditation and its incorporation in the school setting. In this regard, the state of the art explored highlights significant experiences of meditation in classrooms. Briefly, its general benefits in man have been proven. Now, what arguments should be fenced off to justify the incorporation of meditation in the educational field?
Keywords: meditation; school contexts; uncertainties; reflections